A Low-Cost Social Robot for Gesture-Based Educational Activities and Human-Robot Interaction in Learning Environments - Bastos, Ana Caroline De O.; Pinto, Milena F.; Coutinho, Rafaelli C.; Silva, Fabricio L.; Lima, Amaro A. De; Araujo, Gabriel M. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This work presents the design and implementation of a low-cost social robot intended for use in educational environments. The robot is constructed using affordable materials such as cardboard and PVC, and uses Arduino-compatible components for actuation and control. It is capable of recognizing and mimicking basic human gestures, such as waving, nodding, and head-shaking, through computer vision techniques using MediaPipe and OpenCV. The system architecture combines gesture recognition, real-time communication, and servomotor actuation to simulate socially meaningful interactions. Beyond its technical capabilities, the robot aims to enhance classroom en-gagement, support socio-emotional learning, and promote hands-on experiences in robotics and programming. The platform is designed for replicability and accessibility, making it particularly suited for public schools and STEM education initiatives.